b y Peter and Connie Roop ; illustrated by Carol Schwartz. - Roop, Peter; Roop, Connie; Schwartz, Carol, 1954- (New York : Scholastic, 2006)
Simple rhyming text describes the behavior of whales and dolphins, including singing, diving, playing, and eating.
Text in Arabic.
K-3
Translation of: Whales and dolphins.
Title supplied by OCLC WorldCat.
Keywords: Whales -- Juvenile literature; Dolphins -- Juvenile literature; Cetacea -- Juvenile literature; Whales; Dolphins; Arabic language materials; Whales; Dolphins; Arabic language